Nanoplatforms for Delivery of siRNA to the Eye - Sarma Kataki, Manjir; Bhusan Kakoti, Bibhuti; Jameson, Melanie; Solanki, Aum; Hirani, Anjali; Pathak, Yashwant (Current Pharmaceutical Design, 2015)
Drug delivery to the eye is challenging for formulation scientists due to physiological barriers that separate the eye from the rest of the body. A variety of ocular disorders demand the development of optimal drug delivery systems for the administration of drugs and therapeutic agents that can overcome barriers that restrict drug bioavailability. SiRNA inhibits the expression of target genes and has immense potential as a biological tool for the therapeutic inhibition of disease causing genes; however, delivery of siRNA to ocular tissue is a challenge. Recent literature suggests that nanoplatforms show great promise in enhancing ophthalmic drug delivery. A drug delivery system involving nanoparticles and siRNA could surpass problems faced in ocular delivery with improved biodistribution and lower toxicity. This review covers recent research in the area of nanocarrier siRNA drug delivery for various ocular disorders.
Keywords: dendrimers